The Effect of Buffer addition on Anaerobic Medium with Carboxyl-Methyl-Cellulose Ascarbone Sources And Cellulase Induseron Rumen Cellulolytic Microorganisms degradation - Bachruddin, Zaenal; Kurniawati, Asih; Hanim, Chusnul; Fradita, Yuvanta Lia; Yusiati, Lies Mira (2015)
This research was aimed to study of the effect of buffer addition on rumen cellulolytic microorganisms degradation of anaerobic medium that consist of carboxyl-methyl –cellulose (CMC) as carbon source and celluase induser. Celluase is an enzyme which acts in celluose into simple glucose. Liquid medium MRS with PH of 3.8 was added to CMC 1% as a carbon source as well as cellulose induser, and rumen liquid as a source of microbes. The treatment was NaHCO3 buffer addition in the liquid medium with the level of addition of 0, 0.1%, 0.2%, 0.5%, 0.75% dan 1%. The microbe growth was identified using Hungate tube for 24 hours at 39oC with 3 replication. At the end of fermentation process, the observation was conducted for microbe protein concentration, a residual of reducing sugar, and carbohydrates total. Data were analyzed using one way anova, if there is significant result due to buffer addition, Duncan’s new multiple range test (DMRT) was used to compare means. The result showed that supplementation of buffer NaHCO3 in the medium CMC as carbon source and cellulase inducer gave significant (P,0.05) result toward microbes protein concentration, residual of reducing sugar, and decreasing carbohydrates total (P<0.05). It can be concluded that the addition of NaHCO3 buffer will increase the medium pH and the activity of rumen cellulolitic bacteria will be affected because there was an increase in microbes protein number, carbohydrate total, and residual of reducing sugar.